Literasi Multikultural Digital dalam Pendidikan Agama Islam: Analisis Representasi Nilai Multikultural pada Video TikTok Habib Ja’far - Miftahul Adila Fitria; Lathifatul Izzah (Lembaga Yasin AlSys, 2026)
Although digital dakwah and digital literacy have been widely examined, studies that specifically address the implicit representation of multicultural values in short-form social media videos, particularly on TikTok, remain limited. This study aims to analyze how multicultural values are represented in digital dakwah content in Habib Ja’far’s TikTok videos and to explore its implications for Islamic Religious Education in the digital era. The study employed a qualitative approach with a digital content analysis design. Data in the form of TikTok videos were purposively selected based on dakwah content and the relevance of multicultural values, collected through video documentation, narrative transcription, and a review of relevant scholarly literature, and then analyzed using thematic analysis techniques. The findings show that the values of tolerance, inclusivity, religious moderation, and communication ethics are consistently represented through everyday narratives, the use of inclusive language, reflective humor, and non-confrontational message framing. These results contribute to the development of the concept of digital multicultural literacy by demonstrating that the value of diversity can be communicated implicitly through dakwah communication practices on social media. The study concludes that humanistic communication strategies are crucial in digital dakwah and recommends that Islamic Religious Education (PAI) educators utilize digital dakwah content as contextual learning resources to support inclusive PAI learning in the digital era, while opening opportunities for further research on audience reception and the pedagogical effectiveness of multicultural digital dakwah.